Information communication technology use in post-graduate diploma in education at Tribhuvan University - Pokhrel, Rajendra Kumar; Pokhrel, Anju (Univeritas Papua, 2025)
The application of ICT in education has made education accessible and affordable and has introduced a new way of learning through digital platforms. Tribhuvan University, Faculty of Education, Dean's Office, has introduced a Post Graduate Diploma (PGD) programme in education. The programme has been introduced as an alternative to the university's traditional One Year Bachelor of Education. The blended teaching method is employed in this programme. The main objective of this research is to analyse the use of information communication technology (ICT) in the Post-Graduate Diploma course at Tribhuvan University, with specific objectives that include analysing the economic benefits of ICT use and exploring its affordability for Post-Graduate Diploma students. The study employed a mixed-methods research design. The study population consisted of all PGDE students enrolled at Tribhuvan University. A questionnaire and an interview were conducted to collect data and information. The research data was analysed in two stages. In the first stage, primary data and information for quantitative analysis were collected using a pre-structured questionnaire and were analysed using simple statistical tools. In the second stage, the qualitative data and information were derived from key informant interviews (faculty members and campus chiefs). The majority of the respondents reported that ICT use in PGDE made education more accessible to students from rural and remote areas. Some respondents viewed ICT tools as remaining challenging to them because of language limitations, as digital platforms are English-oriented.